Hepatic granulomas in a feverish patient. - Capelo, Joana; Carragoso, Adelino (Acta Médica Portuguesa, 2010)
Fever of unknown origin is a diagnostic challenge. When the diagnosis remains elusive despite extensive non-invasive diagnostic studies, it can be necessary to conduct more invasive procedures, such as liver biopsy. We report a male with fever of unknown origin who had tender enlarged liver and raised liver enzymes whose hepatic biopsy disclosed epithelioid granulomas, with the etiological diagnosis made by the positivity of Coxiella burnetii serology.